KARAKTERISTIK ATRIBUT TERHADAP PERILAKU PENGGUNA PADA PUSAT KULINER DI KOPLAKAN BLORA - Dargayana, Glandisepa Chahyanita; Tri H., Suhargo; Rukayah, Siti (Jurnal Arsitektur ARCADE, 2020)
Renovation will not succeed if the designer does not consider user attributes, so the results of the design will be changed according to the needs of user attributes. This happened in Koplakan Blora, which was more spacious and modern, but they complained about the lack of visitors after the renovation. This study aims to determine the characteristics of post-occupant users, interests, responses, and expectations of Koplakan users. Using descriptive qualitative research methods with instrument attributes (comfort, sociality, visibility, legibility) of the user, knowing the relationship between perceptions and user attributes, and knowing the comfortable space settings for the user. The results of the study are based on the required attributes, the user needs a large counter, the location of the sign that is easily visible to visitors, the size of a low counter barrier to be able to socialize with other traders, the shape of the building that is in accordance with the local culinary center